Editorial: Against Subject Datafication through Anti-Oppressive Data Practices - Renato Bernasconi (Diseña, 2021)
This editorial participates in the discussion proposed by the guest editors of this issue by emphasizing that researchers who produce, manipulate, and interpret datasets will be contributing to the entrenchment of an oppressive regime of power-knowledge, if they do not begin their work by reflecting on the dynamics of domination and exploitation inherent in data, just as they will only reinforce inequalities and injustices if they do not question, by extension, the illusions of epistemic purity of datafication. Based on a brief literature review, the editorial highlights three useful strategies for transforming data into an anti-oppressive knowledge-power system: connecting data to the context in which it is produced, as stated by D’Ignazio and Klein; making data mining a people-centered process, as proposed by Leurs and Shepherd; and using data to produce embodied stories, as suggested by Leurs.